TINJAUAN PENYUSUTAN ASET TETAP PT PLN (PERSERO)PUSAT PENDIDIKAN DAN PELATIHAN JAKARTA - Indria Amani Azzahra, Jara (2022)
Economic level that can be measured in units of assets, including nonfinancial resources and resources needed to provide services to the community. PT. PLN (Persero) Jakarta education and training center is an electricity company dedicated to improving the lives of customers or the community through the use of electric power. Operational activities are supported by the use of fixed assets, for companies, fixed assets have a very important role in producing goods and services. Disclosing how to obtain assets and the method of depreciation of assets used by the company because over time the benefits and value are decreasing. Depreciation of fixed assets in the company must use the applicable standards, for this reason it is very effective and efficient to use provisions in accordance with applicable laws and regulations. PT. PLN (Persero) Jakarta education and training center uses the depreciation of fixed assets using the straight-line method. Keywords: Fixed Assets, Depreciation, Straight Line.